Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/1075547018808298
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Science to Bars: A Strategy for Effective Science Communication

Abstract: It is well accepted that it is part of a scientist’s duty to communicate science, yet most practicing scientists lack the training and opportunity to do so. In this article, we use the framework of science talks in bars to highlight the importance of locality and environment. We propose that science communication programs should be developed around the locales of the target community as an effective strategy to counter the rising mistrust in science and scientists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
(12 reference statements)
1
17
0
Order By: Relevance
“…Both the survey and qualitative component of the evaluation showed that audience members attended PoST because of their interest in science, its entertainment value and their desire to learn; our study shows that audience members indeed enjoyed the event and perceived that they have increased their knowledge. These findings were consistent with evaluations of similar initiatives as the science café-like programs in Cambodia [6], Hong Kong [8], USA [26, 27], the Netherlands [28] and participation in science festivals in the UK [29, 30].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Both the survey and qualitative component of the evaluation showed that audience members attended PoST because of their interest in science, its entertainment value and their desire to learn; our study shows that audience members indeed enjoyed the event and perceived that they have increased their knowledge. These findings were consistent with evaluations of similar initiatives as the science café-like programs in Cambodia [6], Hong Kong [8], USA [26, 27], the Netherlands [28] and participation in science festivals in the UK [29, 30].…”
Section: Discussionsupporting
confidence: 84%
“…It was held on a Saturday afternoon and a different part of the city from the English language events. Location and environment have been identified as determinants for high or low attendance figures [8]. For example, “Nerd Nite” events in Hong Kong have been very well attended due to the location of the events—a bar right in the heart of the business and finance district [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scientists have also used stand-up comedy (Pinto et al, 2015), theater (Dowell & Weitkamp, 2012;Halpern, 2012), and visual art (Ede, 2002) to communicate their ideas to lay people. Others have used scientific information in movies (Valenti, 2011;Valenti, 2016), music videos (Allgaier, 2013), popular music (Huang & Allgaier, 2015), and local bars (Tan & Perucho, 2018). Organizers see such events as ways to inspire trust in scientists, who at times appear aloof and use ambiguous terms that have different meanings in nonacademic settings (Tan & Perucho, 2018).…”
Section: Science-art Collaborationsmentioning
confidence: 99%